ECONOMIC ANALYSIS OF THE ACTIVITIES OF AGROTAXI INDUSTRY CLUSTERS IN THE CONTEXT OF DIGITAL MANAGEMENT - Astanayev, Kulmakhammat Sanayevich (THE INNOVATION ECONOMY, 2026)
This article analyzes the economic performance of agro-industrial clusters in the context of the digital economy. It examines the impact of digital management technologies on agricultural production, processing, and logistics processes. The study found that the implementation of digital technologies in agro-industrial clusters increases production efficiency, optimizes resource use, and improves management processes. Proposals for improving the economic performance of clusters based on digital management are also developed.